Analisis gaya bahasa pengkhususan dalam Surah Hud / Ann Surina Sulaiman - Ann Surina, Sulaiman (2018)
The language style of restriction or uslub al-qasr is a topic in word order of Arabic rhetoric which means “to restrict someone or something by something else”. This study aims to discuss the development of restriction style by analyzing its type, oratory condition, the purpose of its use in Surah Hud and review whether the tools of restrictions (turuq al-qasr) is restricted to a particular situation. This study uses descriptive analysis methodology, beginning with data collection and data analysis by applying discourse analysis method, calculation method, comparison method and historical method. Findings indicate that the restriction style was discussed generally in the work of grammarians. al-Jurjaniy is the scholar who developed it into a separate topic in Arabic rhetoric. The analysis of surah Hud found that hakiki tahqiqiy category are the most widely used, followed by qalbi, hakiki iddi‘a’iy and ifrad. Restrictions in surah Hud are most often used to affirm, confirm, threaten, criticize and urge for the following situations : the disbeliever, the hesitant, affirmation and hint on another meaning. The categories of restrictions does not affect the determination of its purpose in surah Hud, but the purpose itself is in accordance with the oratory situation. Oratory situation may affect the tools of restrictions chosen but the most important factor is the suitability of restrictions tools with sentence structure, whether it is noun sentence or verb sentence. The use of the restriction style in surah Hud conveys the actual meaning accurately and affects the addressee’s feelings. The study also uncovered new findings that the use of exception particle innama in the situation where the addressee deny what’s proven to be true.